2018
DOI: 10.3991/ijim.v12i8.9530
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mobile Phone Usage in Classroom and Academic Achievement in College Life

Abstract: <p>The use of mobile phone has been increasing nowadays in most part of the world and it has become the  phenomenon where people cannot live without. This study aims to reveal whether mobile phone use affects student’s academic achievement compared to other factors such as study program, student’s focus and gender. The frequent of mobile phone use and how excellence student’s academic performance will be analysed. A survey has been conducted to a large number of college students. A questionnaire was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
(13 reference statements)
1
7
1
Order By: Relevance
“…The result of the study shows that the frequent use of mobile phone gave impacts to the low academic performance of the students. Slightly different from previous study's result, Yunita et al (2018) found that use of cell phone is not significantly distract to the students' GPA. In 2014, Lepp et al (2014) explored the same topic but different findings.…”
contrasting
confidence: 99%
“…The result of the study shows that the frequent use of mobile phone gave impacts to the low academic performance of the students. Slightly different from previous study's result, Yunita et al (2018) found that use of cell phone is not significantly distract to the students' GPA. In 2014, Lepp et al (2014) explored the same topic but different findings.…”
contrasting
confidence: 99%
“…However, several other findings disagree with the results of this study. Some stated that gender and study programs taken by students determine the success of smartphone-assisted learning (Yunita, Nursechafia, Setiawan, Nugroho, & Ramadhan, 2018;Zhan, Fong, Mei, & Liang, 2015;P. Hsu, Van Dyke, & Smith, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the potential for reward is clearly to increase motivation, and help teachers to influence the process and learning outcomes. Gadgets and games have a positive impact on the world of education (Yunita et al, 2018;Fawareh & Jusoh, 2017).…”
Section: Students' Responsesmentioning
confidence: 99%